(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In this project, the irst archaeological discoveries registered in the lands of Michoacán during the 19th century are traced. It describes the eforts to found a museum dedicated to the protection of the cultural heritage inherited from the past, especially collections of archaeological objects, documents, ancient books, newspapers, photographs, ethnographic testimonies of past generations of Michoacán people. Also, the project emphasizes the interest from anthropological studies and concerning indigenous languages, especially Tarasco. It highlights the contributions made to this class of studies by the ecclesiastics José Guadalupe Romero, Francisco Plancarte and Navarrete and Sebastián Olivares, together with those of the doctor Nicolás León and the Norwegian ethnologist Carl Lumholtz.